Distribution and abundance of megrim (Lepidorhombus boscii and Lepidorhombus whiffiagonis) in the northern Spanish shelf. - Sánchez, Francisco; Pérez-Contreras, María Nélida; Landa, Jorge (ICES Journal of Marine Science, 1998)
The distribution and abundance patterns of the two species of megrim Lepidorhombus whiffiagonis L. boscii, in ICES Divisions VIIIc and IXa, were analysed using the data provided by bottom-trawl surveys and the Spanish fishing fleet in European Atlantic waters. The consistency of year-class strengths estimated over time from these surveys was taken as an indication of the reliability of the survey data to monitor megrim population abundance. Recruitment strength was, to a large extent, the main factor governing abundance found in successive years. This is due to the fact that the greater percentage of accessible biomass comprises 1, 2 and 3-year-old individuals. Four spot megrim (L. boscii) is currently the most abundant species in this zone due to the weak recruitment of L. whiffiagonis in recent years. As a consequence of these species' sexual differences in growth, there is a predominance of females in the larger-sized individuals of the population. From 4 years onwards, males show a higher mortality rate than females. No evidence of geographical migrations was found, although a bathymetric expansion occurs with age: juveniles are more stenobathic than adults are. A degree of specialization can be observed in the two species' habitats, probably due to their different feeding systems, with L. whiffiagonis occupying shallower waters. Production statistics from the Spanish fishing fleet in the north-east Atlantic show a far wider distribution of L. boscii than was indicated by data available previously. Sí